Предмет: Математика,
автор: miavolna666
Выполните умножение:
-2ab²*(3a²b-5ab²).Найдите значение полученного многочлена при b=-1,a=-1.
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
-2ab^2*a*b(3a-5b)=-2a^2*b^3*(3a-5b)
-2*(-1)^2*(-1)^3*(3*(-1)- 5*(-1))=-2*1*(-1)*(-3+5)=4
Автор ответа:
2
Ответ:
-2ab²*(3a²b-5ab²) = -6a³b³ + 10a²b⁴
-6(-1)³(-1)³ + 10(-1)²(-1)⁴ = -6+10 = 4
Похожие вопросы
Предмет: География,
автор: kfpwngd2fs
Предмет: Математика,
автор: sem2007smirmow
Предмет: Русский язык,
автор: nelakr693
Предмет: Математика,
автор: антіпов
Предмет: География,
автор: МиколаКирилюк